Information Networking and its Application in the Digital Era with illustration from the University of Port Harcourt Library - Umeozor, Susan Nnadozie (International Journal of Knowledge Content Development & Technology, 2019)
This paper discussed the factors that necessitated information networking, types of networks, benefits of information networking, library information networking and the University of Port Harcourt library network initiatives. Information networking is a process of communication, exchange of ideas, resource sharing and collaboration between individuals, organizations, institutions and libraries and it is facilitated by ICTs and the internet for improved accessibility. It has been brought about by information explosion, rapid advancement in information communication technologies, inadequate funding and increased demand for quality information. Networks can be classified into local, national, regional, and international networks and are formed to serve different categories of user communities. Benefits of information networking include resource sharing, on-line conferences and participation in programmes at distant centers, collaboration among scholars in different countries, and communication flow through the internet, social media, and electronic mail. Library information networking started with the interlibrary loan which has metamorphosed into library consortia in which groups of libraries partner to coordinate activities, share resources and combine expertise. The University of Port Harcourt Library network initiatives started with an e-granary (a CD ROM) and the establishment of a local area network. It had transited from Card Catalogue to Online Public Access Catalogue (OPAC) and now has a website devoted to library services. The library has subscribed to more than 15 electronic databases and has updated to include automated circulation and cataloguing services. Information networking has greatly improved the sharing of resources in information acquisition and dissemination since no single institution can acquire the overwhelming number of information resources in their various formats in the reality of the current information explosion. URL: http://ijkcdt.net/xml/20257/20257.pdf